Electron microscopic features of the lacrimal sac mucopeptide concretions - Mohammad, Javed Ali; Schicht, Martin; Heichel, Jens; Nadimpalli, Siva Kumar; Paulsen, Friedrich (Graefes Archive For Clinical and Experimental Ophthalmology, 2018)
PURPOSE: The aim of this study was to examine the ultrastructural features of the mucopeptide concretions obtained from the lacrimal sac. METHODS: Mucopeptide concretions obtained from the lacrimal sacs of 10 patients during a dacryocystorhinostomy were immediately fixed for electron microscopic analysis. The surfaces were studied separately and longitudinal and transverse ultra-thin sections were obtained at different levels and all were studied using the standard protocols of scanning electron microscopy (SEM) and transmission electron microscopy (TEM). RESULTS: Mucopeptide concretions based on their extent take the shape of the lacrimal sac and nasolacrimal duct. The external surfaces and cut sections show mostly areas of homogenous deposits with occasional intervening heterogenic areas. Two distinct types of craters were noted, mostly in the heterogeneous areas. The core of the concretions was made up of extensive networks of fibril like tangles filled predominantly with granular material and red blood cells with occasional presence of granulocytes and epithelial cells. Numerous vacuoles and fissures appear to be more of artifacts than any metabolic process. No organic fibers of fungal filaments were noted within the concretions. There was no evidence of any bacterial biofilms other than few focal areas of scattered bacteria. Possible events in the development of mucopeptide concretions have been hypothesized based on the ultrastructural findings. CONCLUSION: Ultrastructural features of mucopeptide concretions from the lacrimal sac help in better understanding of their etiopathogenesis and tissue interactions. Further exploration of different stages of a concretion is needed to understand the potential factors that trigger its genesis and evolution.
EVALuna2:35315